The results of determining the indicators of the morphological composition of the blood of animals and individual biochemical indicators using a potential drug with a mixture of two active compounds: 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole-3-yl)methyl)morpholine and 5-(2-fluorophenyl)-4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol in milk thistle seed oil - M. V. Ohloblina; I V. Bushuieva; V. V. Parchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The introduction of new domestic highly effective and safe medicines into medical and veterinary practice is an important task of modern pharmaceutical science. Continuation of the search and conduct of research to bring the biological activity of 1,2,4-triazole derivatives is one of the promising areas of such activity. At this stage of research, it is known that such 1,2,4-triazole derivatives as 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole-3-yl)methyl)morpholine and 5-(2-fluorophenyl)-4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol have a wide spectrum of biological activity. Interest for further thorough research is precisely the antimicrobial and antifungal effects. The introduction into medical and veterinary practice of newly created drugs for the treatment of fungal diseases on the skin of animals requires further studies of the properties of these compounds and their mixtures.